Robust hollow glass microspheres-based solar evaporator with enhanced thermal insulation performance for efficient solar-driven interfacial evaporation. (December 2022) - Wang, S.; Niu, Y.; Mu, W.; Zhu, Z.; Sun, H.; Li, J.; Liang, W.; Li, A.
Abstract: Solar-driven interfacial evaporation is a green and efficient technology with wide applications, such as seawater desalination, wastewater treatment and electrical generation, and so on. Herein, we report a novel composite aerogel (PI-MWCNT-MHGM) using (3-aminopropyl)triethoxysilane modified hollow glass microspheres (MHGM), carboxylated multiwalled carbon nanotubes (MWCNT), and water-soluble polyamide via simple directional freezing and freeze-drying methods for solar-driven interfacial evaporation. Owing to the directional freezing method, the hollow structure of HGM, and strong chemical interactions in PI-MWCNT-MHGM, the PI-MWCNT-MHGM composite aerogel exhibits porous structure with vertically aligned channels, strong mechanical properties, low thermal conductivity, and excellent thermal insulation, as well as broadband light absorption. As expected, the PI-MWCNT-MHGM evaporator shows a high evaporation rate (1.506 kg m −2 h −1 ) under 1 kW m −2 solar irradiation and excellent salt resistance, e.g., even when 1 g of NaCl was placed on the surface of the PI-MWCNT-MHGM, it could dissolve within 10 min. Moreover, the PI-MWCNT-MHGM possesses self-floating ability, combined with its eco-friendly, facile, and potentially scalable preparation method, the prepared aerogel may hold great potential for real applications. Graphical abstract: Image 1 Highlights: The novel evaporator (PI-MWCNT-MHGM) with vertically aligned channels. The evaporator exhibits low thermal conductivity and mechanical robustness. The evaporator possesses self-floating ability and eco-friendly. The PI-MWCNT-MHGM evaporator shows a high evaporation rate (1.506 kg m −2 h −1 ). The evaporator shows excellent salt-resistant performance even in 20 wt% NaCl.